Decline in sediment contamination by persistent toxic substances from the outfall of wastewater treatment plant: Effectiveness of legislative actions in Korea. (June 2016) - Jin, Xiangzi; Lee, Hyun-Kyung; Badejo, Abimbola C.; Lee, Sang-Yoon; Shen, Aihua; Lee, Sunggyu; Jeong, Yunsun; Choi, Minkyu; Moon, Hyo-Bang
Abstract: Legacy and new persistent organic pollutants (POPs) and polycyclic aromatic hydrocarbons (PAHs) were measured in sediments near a wastewater treatment plant (WWTP) outfall in a semi-enclosed bay, to investigate the current contamination and temporal changes in these contaminants associated with regulation activities in Korea. The concentrations of most of the POPs showed clear decreasing trends with an increase in the distance from the WWTP outfall, indicating that the WWTP discharges greatly contributed to the sediment contamination by POPs. Highly significant correlations were found for most of the POPs, indicating a common source for sediment contamination. Significant declines were found in the concentrations of polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs), dioxin-like polychlorinated biphenyls (DL-PCBs), polybrominated diphenyl ethers (PBDEs), and PAHs in the sediments collected between 2005 and 2013. This result suggested that legislative actions (regulation of the PCDD/Fs in flue gas, total pollution load management, and whole effluent toxicity for WWTP discharges) and change of fuels, were likely to be effective at reducing the POP and PAH levels in sediments during the past several years. The different compositional profiles of the PCDD/Fs and PAHs between 2005 and 2013 implied changes in and/or additional sources of these contaminants. Despite a decline in the PCDD/Fs over time, the present levels of PCDD/Fs in the sediment exceeded some of the sediment quality guidelines suggested by the National Oceanic and Atmospheric Administration. Graphical abstract: Highlights: Clear decreasing trends in the POPs were observed with an increase in the distance from the WWTP outfall. Significant declines were found in the PCDD/Fs, dioxin-like PCBs, PBDEs, and PAHs during past years. Legislative actions were likely to be effective for reducing the POPs and PAHs in sediments. Current PCDD/F levels in the sediments near the WWTP outfall exceeded the sediment quality guidelines.